Drawing the Profile of Students of English as Dictionary Users - HAMDI, Chaker (Journal of Human Sciences, 2014)
Fifty freshmen students of English took part in a study in order to establish their profile as dictionary users. The respondents completed a questionnaire regarding the types of dictionaries they used, the frequency of use, the main reasons for consultation, the difficulties in the lookup process, instruction in dictionary use, etc. The analysis of data revealed that the students use monolingual dictionaries (MLDs) more frequently than bilingual dictionaries (BLDs), and that the difficulties they have in the lookup process are due to deficiencies in their dictionaries. In addition, the results provide evidence that our students do not take full advantage of their monolingual dictionaries because they hardly make use of the appendices and usage guides in them. The findings also indicate that their dictionary skills are more or less weak. Therefore, this study suggests that our students should receive more training in dictionary use so that they enhance their skills and make the most of their dictionaries.